(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Nutraceuticals are biologically active compounds derived from natural food sources that provide health benefits beyond basic nutrition, including the prevention and management of chronic diseases. Among them, resveratrol, a non-flavonoid polyphenolic phytoalexin found mainly in grapes, red wine, peanuts, and berries, has gained significant attention for its potential role in cardiovascular disease (CVD) prevention. Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide, largely driven by oxidative stress, chronic inflammation, endothelial dysfunction, dyslipidemia, hypertension, and abnormal platelet aggregation. Resveratrol exerts its effects by modulating key signaling pathways, including SIRT1, AMPK, Nrf2, NF-κB, and eNOS, thereby enhancing nitric oxide bioavailability, reducing oxidative stress and inflammation, improving endothelial function, inhibiting platelet aggregation, and regulating lipid metabolism. Preclinical and clinical studies suggest beneficial roles of resveratrol in atherosclerosis, hypertension, myocardial infarction or stroke, endothelial dysfunction, and heart failure. Overall, resveratrol shows strong potential as a safe, natural, and multifunctional nutraceutical for cardiovascular disease prevention and as an adjunct to conventional therapies, although further large-scale clinical trials are required to establish optimal dosage, long-term safety, and clinical effectiveness. However, translation of these promising findings into clinical practice remains constrained by limited human clinical evidence, heterogeneity in study design, short intervention durations, small sample sizes, and substantial variability in clinical outcomes. Furthermore, the clinical utility of resveratrol is hindered by poor oral bioavailability, rapid metabolism, uncertain dose–response relationships, and lack of standardized formulations. Emerging strategies, including micronized, encapsulated, and nano-based delivery systems, may enhance systemic availability and therapeutic efficacy. In conclusion, resveratrol represents a compelling nutraceutical candidate for cardiovascular protection, yet definitive validation through large-scale, well-designed human clinical trials with standardized formulations, optimized dosing, and clinically relevant cardiovascular endpoints is essential before its routine incorporation into CVD prevention and treatment strategies.